1997
DOI: 10.1016/s0194-5998(97)70179-7
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear nucleus cell size changes in the dalmatian: Model of congenital deafness

Abstract: We assessed cellular changes in one population of neurons of the cochlear nucleus associated with a form of genetic deafness in deaf dalmatians. Spheric cells from deaf dalmatians and age-matched control (hearing) dogs were analyzed morphometrically. The somatic silhouette of these cells was reduced by 22.1% to 38.1%. The effect on cell size was greater with increased duration of deafness. Because the deaf dalmatian exhibits progressive degeneration of the auditory periphery, shrinkage of spheric cells may ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…There were also significant decreases in labeled cells in the lateral cortex in both the ventral (32%, p < 0.01) and dorsal (47%, p <0.04) regions. In the lateral cortex the medium sized cells were most affected by deafness, becoming a smaller proportion of those retaining label, However, we cannot rule out that there may be decreases in cell size, as reported to occur with deafening (Kawano et al, 1997;Lesperance et al, 1995;Lustig et al, 1994;Niparko, 1999;Niparko et al, 1997;Sie et al, 1992;Willott et al, 1994). Such a decrease in cell size could bring neurons from a previous classification of medium sized to the class of small neurons.…”
Section: In Situ Hybridizationmentioning
confidence: 79%
See 1 more Smart Citation
“…There were also significant decreases in labeled cells in the lateral cortex in both the ventral (32%, p < 0.01) and dorsal (47%, p <0.04) regions. In the lateral cortex the medium sized cells were most affected by deafness, becoming a smaller proportion of those retaining label, However, we cannot rule out that there may be decreases in cell size, as reported to occur with deafening (Kawano et al, 1997;Lesperance et al, 1995;Lustig et al, 1994;Niparko, 1999;Niparko et al, 1997;Sie et al, 1992;Willott et al, 1994). Such a decrease in cell size could bring neurons from a previous classification of medium sized to the class of small neurons.…”
Section: In Situ Hybridizationmentioning
confidence: 79%
“…As such, one modality for TREK-2 activation is through mechanical gating via stretching the cell membrane (Kim et al, 2005). Decreases in cell size (Kawano et al, 1997;Lesperance et al, 1995;Lustig et al, 1994;Niparko, 1999;Niparko et al, 1997;Sie et al, 1992;Willott et al, 1994) or even flattening of synapses (Gulley et al, 1978;Ryugo et al, 2005) that have been reported following deafness could therefore influence TREK-2 activity and expression. It is interesting that the deafness-associated decrease in TREK-2 expression was transient, significant only at 3 days following deafness, while decreases in the other three subunits were more sustained.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant degeneration of the spiral ganglion neurons and degenerative changes in the CN still occur. A reduction of 25-50% in total volume of the CN and a decrease of 20-40% in spherical cell body size in the AVCN has been reported in cats deafened by ototoxic drugs as neonates (Hultcrantz et al, 1991;Lustig et al, 1994;Hardie and Shepherd, 1999;Osofsky et al, 2001;Leake et al, 2006) and in congenitally deaf animals (Saada et al, 1996;Niparko and Finger, 1997).…”
Section: Introductionmentioning
confidence: 92%
“…There have been numerous reports of deafness-associated decreases in cell size in the cochlear nucleus (Kawano et al, 1997;Lesperance et al, 1995;Lustig et al, 1994;Niparko, 1999;Niparko and Finger, 1997;Sie and Rubel, 1992;Willott et al, 1994). One modality for the activation of TREK is through mechanical gating via stretching the cell membrane .…”
Section: Cell Volume Regulationmentioning
confidence: 99%